Collagen from Atlantic cod (Gadus morhua) skins extracted using CO2 acidified water with potential application in healthcare - Sousa, Rita O. (2020)
This work has received funding from European Union, under the scope of European Regional Development Fund (ERDF) through the Structured Project NORTE-01-0145-FEDER-000021 (Norte2020) and under the scope of the European Union Seventh Framework Programme (FP7/2007-2013) through grant agreement ERC-2012-ADG 20120216-321266 (ERC Advanced Grant ComplexiTE). PhD grant of C. O. (Norte-08-5369-000037) with financial support by Norte 2020. The authors would like to acknowledge Frigoríficos da Ermida, Lda. (Gafanha da Nazaré, Portugal) for the kind offer of Atlantic cod skins and to Dr. Manuela Pintado, Dr. Raquel Madureira and Joana Costa (Universidade Católica Portuguesa, Porto) for the use of microDSC and assistance during measurements. The authors also thank to Dr. Catarina Marques and Dr. Sandra Pina (3B’s Research Group) for assistance on XRD measurements, to Dr. Rita Lopez-Cebral (3B’s Research Group) for assistance on SEC measurements and to Dr. Alexandre Barros for discussions.